Advanced Glycation End Products Induce Obesity and Hepatosteatosis in CD-1 Wild-Type Mice. (31st January 2016) - Sayej, Wael N.; Knight III, Paul R.; Guo, Weidun Alan; Mullan, Barbara; Ohtake, Patricia J.; Davidson, Bruce A.; Khan, Abdur; Baker, Robert D.; Baker, Susan S.
Abstract : AGEs are a heterogeneous group of molecules formed from the nonenzymatic reaction of reducing sugars with free amino groups of proteins, lipids, and/or nucleic acids. AGEs have been shown to play a role in various conditions including cardiovascular disease and diabetes. In this study, we hypothesized that AGEs play a role in the "multiple hit hypothesis" of nonalcoholic fatty liver disease (NAFLD) and contribute to the pathogenesis of hepatosteatosis. We measured the effects of various mouse chows containing high or low AGE in the presence of high or low fat content on mouse weight and epididymal fat pads. We also measured the effects of these chows on the inflammatory response by measuring cytokine levels and myeloperoxidase activity levels on liver supernatants. We observed significant differences in weight gain and epididymal fat pad weights in the high AGE-high fat (HAGE-HF) versus the other groups. Leptin, TNF- α, IL-6, and myeloperoxidase (MPO) levels were significantly higher in the HAGE-HF group. We conclude that a diet containing high AGEs in the presence of high fat induces weight gain and hepatosteatosis in CD-1 mice. This may represent a model to study the role of AGEs in the pathogenesis of hepatosteatosis and steatohepatitis.